QUR’ANIC INTERPRETATION IN PESANTREN: MECHANISMS AND AUTHORITY OF K.H. MAIMOEN ZUBAIR - Anam, Saichul; Millat Ahamad, Nehru; Rahman Nor Afif Hamid, Abdur; Karim, Abdul (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
This study aims to analyze the mechanisms and authority underlying K.H. Maimun Zubair’s interpretations as reflected in Tafsir Safīnah Kallā Saya’lamūn, a work documented by his student, Ismail Al-Ascholīy. Mbah Moen’s interpretations are often perceived as deeply intertwined with contextual nuances, yet the factors influencing these interpretations and the processes involved in their formulation remain insufficiently examined. This research seeks to bridge this gap by uncovering the intricate processes behind his interpretative approach, particularly concerning contemporary themes. Employing qualitative methods with a literature-based analysis, the study reveals that multifaceted dimensions, including historical and psychological contexts shape Mbah Moen’s interpretations. His engagement with a conducive intellectual environment fosters a contextual interpretative framework that aligns with modern phenomena. Furthermore, his interpretations are deeply rooted in the pesantren tradition, which significantly informs his intellectual orientation. Within this framework, the authority of the Qur’an, historical narratives, and classical exegetical works remains pivotal. Nonetheless, Mbah Moen adeptly integrates modern perspectives into his interpretations, demonstrating a capacity to contextualize Qur’anic texts in ways that transcend conventional exegetical paradigms.